Housewives' Role in Protecting the Environment Through Recycling Cement Bags with Ecoprint - Fidiana Fidiana; Triyonowati Triyonowati; Endang Dwi R; Budiyanto Budiyanto; Dini Widyawati; Widhi Rochdianingrum (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Maintaining the sustainability of the environment is a shared responsibility. This effort can be made by recycling existing waste. One of the wastes that has the potential to be reprocessed is cement bag waste. These cement bags have the characteristics of thick paper, no pattern, and neutral base color. Based on these characteristics, the ecoprint technique is a suitable choice. Ecoprint is considered suitable because it uses natural materials that do not damage the environment, and the motif patterns are obtained from leaves and flowers that fall in the environment around the house. This processing technique uses raw materials from the surrounding environment and can maximize organic waste in the surrounding environment. The results of this process can be used as home decoration, bags, and hats with a high and exclusive selling value. The selling price of ecoprint products for bags is around $15-$25. Wall displays are around $10-$20, depending on the type of item and how it is done.